Strategic Decision Policy of Public Service Agency as Government Institution: Analysis of Government Financial Performance - Diana, Shinta Rahma; Limakrisna, Nandan (International Journal of Economics and Financial Issues, 2018)
This study will assess whether the strategic decision policy of having public service agency in a government institution will result in a good value by observing government financial performance using EVA (applying Financial Accounting Standard and Financial Government Standard). Research contributions: (i) will be used to evaluate policies that are already running, if EVA shows a positive number, it is necessary to consider strategic decision of Public Service Agency discontinue in a government institution, for Public Service Agency will offer more value if it is properly managed; (ii) getting the EVA value which is calculated using the basis financial statements that are guided by two reporting standards, Financial Accounting Standard and Government Accounting Standard. Secondary data will be used in this research. Specifically, data of 2014 and 2015 in which during those years, Aerospace Technology Utilization Center LAPAN still served as a Public Service Agency. Data analysis method used is quantitative descriptive method. The results of the study show that both using financial data based on Financial Accounting Standards and Government Accounting Standards, Aerospace Technology Utilization Center LAPAN as a working unit of Public Service Agency, has a good performance as indicated by positive EVA results in 2014 and 2015. This can be used as a consideration for LAPAN in evaluating its policies. Keywords: Government, Public Service Agency, Economic Value Added, SAK, SAP JEL Classifications: G32, G38, G28 DOI: https://doi.org/10.32479/ijefi.7287